Ibsenite Protagonists at Extreme Odds with the Rest of the World: A Psychological Interpretation - Huq, ABM Monirul; Ahsan, Md Firoz Mahmud (Stamford Journal of English, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/sje.v7i0.14470 Stamford Journal of English; Volume 7; Page 145-158